Enlarged Perivascular Spaces and Cerebral Small Vessel Disease in Spontaneous Intracerebral Hemorrhage Patients - Wang, Xin; Feng, Hao; Wang, Yu; Zhou, Jian; Zhao, Xingquan (Frontiers in Neurology, 2019)
Background: Cerebral small vessel disease (SVD) is associated with cognitive decline, depression, increased mortality and disability in stroke patients. MRI-visible perivascular spaces (PVS) are a sensitive neuroimaging marker of SVD. We aimed to explore the risk factors and associations with other SVD markers of PVS in two topographical regions (in the basal ganglia [BG] and centrum semiovale [CS]) in a cohort of spontaneous intracerebral hemorrhage (ICH) patients. Method: We included 306 consecutive patients from a prospective spontaneous ICH cohort. We rated perivascular spaces, white matter hyperintensities (WMH), cerebral microbleeds (CMB) and lacunes with validated visual rating scale. We collected clinical information using standardized forms. We predefined severe PVS as score >2 and examined associations between PVS in both BG and CS regions and clinical and imaging markers of SVD by logistic regression. Results: In the multivariable logistic regression, increasing age (OR=1.075; 95% CI=1.038-1.113, p<0.001), high CS PVS degrees (OR=6.906; 95% CI=3.024-15.774, p<0.001), extensive periventricular WMH (OR=2.878; 95% CI=1.298-6.379, p=0.009), and the presence of CMB (OR=4.073, 95% CI=1.869-8.877, p<0.001) were independently associated with BG PVS severity. Alcohol-drinking habit (OR=2.805; 95% CI=1.451-5.422, p=0.002), hyperlipidemia history (OR=3.782; 95% CI=1.582-8.783, p=0.003), high BG PVS degrees (OR=6.293; 95% CI=2.755-14.371, p<0.001) and the presence of strictly lobar CMB (OR=2.556, 95% CI=1.285-5.085, p=0.008) were independent predictors of increased CS PVS severity. Conclusion: MRI-visible PVS in BG and CS regions are inter-related and have different risk factors in spontaneous ICH patients. Further studies are needed to explore the mechanism and clinical importance of PVS, with possible implications for cerebrovascular disease prevention and effective treatments.